Ethical issues in human movement research - Olivier, Stephen Chris (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1989)
In acknowledging past abuses of humans in research contexts, and recognising the potential for malpractices in Human Movement Studies (HMS), this study evaluated the extent to which ethical issues are addressed in the discipline. The primary method consisted of the standard techniques of philosophic analysis, with empirical data complementing the conclusions. In general, the study contends that insufficient attention is paid to ethical issues in HMS research. In response to a set of specifically constructed, ethically problematic research proposals, only 1.8% of comments from senior researchers advocated rejection of the proposals on ethical grounds. Also, a journal search indicated that consideration of ethical issues in published research may largely be absent. Questionnaire responses revealed that South African HMS departments may be deficient in terms of accountability towards ethical guidelines. Whilst noting the existence of utilitarian ethics in HMS research, it is advocated that deontologic principles should take precedence. Further, only a sound educative effort will produce improvements. In conclusion, this study advocates a deontology-based approach to research ethics. This is consistent with the contention that the use of humans in research is a privilege, and that the rights of participants ought to outweigh the desire of researchers to conduct research.
Keywords: Human mechanics; Human mechanics -- Research -- Moral and ethical aspects; Research -- Moral and ethical aspects